Layered Double Hydroxide Zn/M3+ (M3+= Al and Cr) as Highly Efficient Adsorbent of Heavy Metal Pb(II) - Zaqiya Artha Zahara; Luna Silaen; Normah Normah; Novie Juleanti; Neza Rahayu Palapa (Indonesian Journal of Material Research, 2023)
Synthesis of Zn-Al and Zn-Cr LDHs in this research was successfully carried out. The sucsessfully results can be seen from the XRD characterization which displays diffraction angles at 10 and 60 which indicates the presence of layered structures and anions. FT-IR data displays the presence of nitrate groups at wavenumber 1381 cm−1. BET data shows surface area of Zn-Al and Zn-Cr at 1.965, 31.638 m2/g, corresponding. pHpzc determination of Zn-Al material gets a pH below pHpzc which is 6.2 while Zn-Cr is at pHpzc which is 7.6. Able of Zn (Al/Cr) as adsorbent to adsorp Pb(II) was investigated through several parameters such as kinetics, isotherms, thermodynamics. Kinetic Adsorption for Zn-Al inclined follow PSO, while Zn-Cr follow PFO. Isotherm parameter for Zn-Al and Zn-Cr is Freundlich with a maximum adsorption capacity 74.127 mg/L, and 27.027 mg/L. Thermodynamic process shows that Zn-Al and Zn-Cr LDHs take place in endothermic and spontaneously.